Effects of vitamin d on apoptosis and betatrophin in the kidney tissue of experimental diabetic rats - Demircan, Selçuk; Önalan, Erhan; Kuloğlu, Tuncay; Aydın, Süleyman; Yalçın, Mehmet Hanifi; Gözel, Nevzat; Dönder, Emir (Mattioli 1885, 2020)
The aim of this study is to investigate the effects of vitamin D on betatrophin and apoptosis in rats kidney tissue using an experimental diabetes model created with streptozotocin (STZ). 41 male Wistar-albi-no breed rats were assigned to 5 groups, which included 3 groups consisting of 7 animals each and 2 groups consisting of 10 animals each. The control group received no treatments. Single-dose 0.1 M sodium buffer was administered ip to the Buffer group. The Vitamin D group was orally administered 200 IU/day vitamin D. The Diabetes group was injected ip with single-dose 50 mg/kg STZ by dissolving the material in 0.1 M sodium buffer. Subjects with a glucose level exceeding 250 mg/dl were accepted to be diabetic. The Diabetes + Vitamin D group was injected ip with 50 mg/kg single-dose STZ by dissolving the material in 0.1 M sodium buffer. Once diabetes was established, 200 IU/day vitamin D was administered orally. Rats in all groups were decapitated in the end of the experiment, their kidney tissues were promptly extracted and TUNEL stained with immunohistochemistry. Additionally, serum samples acquired from all groups were evaluated with regard to total antioxidant status (TAS) and total oxidant status (TOS) levels. The histological and bio-chemical analyses of the Control, Buffer, and Vitamin D groups revealed similar serum TOS and TAS levels, and TUNEL positivity and betatrophin immunoreactivity. While the Diabetes group showed significantly higher TOS levels and TUNEL positivity compared to the Control group, their TAS levels and betatrophin immunoreactivity were significantly reduced. The Diabetes+Vitamin group demonstrated significantly lower TOS levels and TUNEL positivity compared to the Diabetic group, and their TAS levels and betatrophin im-munoreactivity increased significantly. In conclusion; experimental diabetes was found to increase TOS and apoptotic cells and decrease TAS and betatrophin levels in kidney tissue in experimental diabetes, and that administering VitD as treatment caused a decrease in TOS and apoptotic cells and an increase in TAS and betatrophin levels. It was concluded that future studies needed to investigate various experimental diabetes times so that the role of diabetes in the pathophysiology of its effect on kidney tissue could be uncovered. (www.actabiomedica.it). © Mattioli 1885.
Keywords: Betatrophin; Diabetes mellitus; Kidney; Streptozotocin